Quantifying the climate effects of bioenergy – Choice of reference system - Koponen, Kati; Soimakallio, Sampo; Kline, Keith L.; Cowie, Annette; Brandão, Miguel (Renewable & sustainable energy reviews, 2018)
In order to understand the climate effects of a bioenergy system, a comparison between the bioenergy system and a reference system is required. The reference system describes the situation that occurs in the absence of the bioenergy system with respect to the use of land, energy, and materials. The importance of reference systems is discussed in the literature but guidance on choosing suitable reference systems for assessing climate effects of bioenergy is limited. The reference system should align with the purpose of the study. Transparency of reference system assumptions is essential for proper interpretation of bioenergy assessments. This paper presents guidance for selecting suitable reference systems. Particular attention is given to choosing the land reference. If the goal is to study the climate effects of bioenergy as a part of total anthropogenic activity the reference system should illustrate what is expected in the absence of human activities. In such a case the suitable land reference is natural regeneration, and energy or material reference systems are not relevant. If the goal is to assess the effect of a change in bioenergy use, the reference system should incorporate human activities. In this case suitable reference systems describe the most likely alternative uses of the land, energy and materials in the absence of the change in bioenergy use. The definition of the reference system is furthermore subject to the temporal scope of the study. In practice, selecting and characterizing reference systems will involve various choices and uncertainties which should be considered carefully. It can be instructive to consider how alternative reference systems influence the results and conclusions drawn from bioenergy assessments.